CITIZEN SCIENCE FOR CLEAN BEACHES: PARTICIPATORY DIAGNOSIS OF MARINE DEBRIS IN MOCHIMA NATIONAL PARK, VENEZUELA - Gamboa, Adriana Carolina; Lemus, Anna Michell Jiménez; Lizardo, Darianys María Isabel Yegres; Vizcaíno, Carlos Dhabriel Pinto (Geosaberes, 2025)
Plastic waste pollution in coastal environments represents one of the main threats to marine biodiversity and ecosystem health. In this context, citizen science emerges as a powerful tool for participatory environmental diagnostics and the strengthening of ecological awareness. This study aimed to characterize the solid waste collected in the community of Mochima, located within the Mochima National Park, Sucre state, Venezuela, through a collaborative monitoring event involving students, teachers, and volunteers. Through activities of collection, classification, and environmental awareness, a total of 673 items were recovered, 74% of which were plastics, with a predominance of single-use bags, bottles, and wrappers. In addition to identifying the composition and predominant colors of the waste, the experience helped strengthen local capacities in environmental analysis, promote non-formal education, and consolidate community co-responsibility values. The results highlight the potential of participatory methodologies to generate useful data, encourage behavioral changes in consumption habits, and contribute to achieving the Sustainable Development Goals, particularly SDG 4, SDG 12, and SDG 14.